Therapeutic Potential of Combined 5% Lifitegrast and Tocopherol Eye Drops in Managing Inflammation and Oxidative Stress in Murine Dry Eye - Jayoung Moon; Enying Jiang; Jingting Liu; Hui Jin; Hee Su Yoon; Hoon-In Choi; Ji Suk Choi; Hong Qi; Hyeon-Jeong Yoon; Kyung Chul Yoon (Pharmaceuticals)
Background/Objectives: This study aimed to evaluate the therapeutic effects of combined 5% lifitegrast (LF) and tocopherol (TCP) eye drops in a murine experimental dry eye (EDE) model. Methods: Female C57BL/6 were divided into seven groups: untreated controls, EDE control, EDE + 0.05% cyclosporin A (CsA), EDE + tocopherol (TCP), EDE + 5% LF, EDE + 5% LF + TCP (once daily), and EDE + 5% LF + TCP (twice daily). Clinical parameters (tear volume, tear break-up time (TBUT), corneal fluorescein staining score (CFSS), tear film lipid layer grade (TFLLG)) were assessed on days 7 and 14. Goblet cell density in the conjunctiva, CD4+ IFN-γ+ T cells, interleukin levels, reactive oxygen species (ROS) levels, and corneal apoptotic cells were analyzed on day 14. Results: Monotherapy with 0.05% CsA and LF showed improvements in all clinical parameters compared to the EDE control (p < 0.05). Combination therapy groups demonstrated superior improvements in clinical parameters compared to the EDE control, 0.05% CsA, and 5% LF groups. CD4+ IFN-γ+ T cell percentages and ROS levels in the cornea and conjunctiva were markedly reduced in the combination groups compared with the 0.05% CsA and 5% LF groups (p < 0.01). Furthermore, corneal apoptotic cells significantly decreased in the combination groups compared to the 0.05% CsA and TCP groups (p < 0.05). Conclusions: Combined 5% LF and TCP eye drops improved tear film parameters and reduced inflammatory and oxidative stress markers. The combination therapy can mitigate ocular surface damage by managing inflammation and oxidative stress in dry eye.